Experiential Learning Theory as a Guide for Experiential Educators in Higher Education - Kolb , Alice Y.; Kolb , David A. (Experiential Learning and Teaching in Higher Education, 2022)
Core concepts of Experiential Learning Theory—the learning cycle, learning style, and learning space—have been widely used by experiential educators in higher education for nearly half a century. We examine the latest thinking about these three concepts and highlight some exemplary applications from the many disciplinary applications of experiential learning in higher education. I think that only slight acquaintance with the history of education is needed to prove that educational reformers and innovators alone have felt the need for a philosophy of education. Those who adhered to the established system needed merely a few fine sounding words to justify existing practices. The real work was done by habits which were so fixed as to be institutional. The lesson for progressive education is that it requires in an urgent degree, a degree more pressing than was incumbent upon former innovators, a philosophy of education based on a philosophy of experience. John Dewey, Experience and Education